GeoTNavi – smart navigation using geo-temporal traffic information. (1st January 2013) - Wang, Shawn; Barua, Susamma; Desai, Kunal; Deshmukh, Swaroop
We introduce a software system GeoTNavi that utilises geo-temporal traffic information in suggesting an optimal route for drivers. GeoTNavi aids the driver in two phases. In the first phase, historical traffic information is studied to reveal patterns on any segment of the highway at a specific day and time. This information is utilised to suggest an optimal route for the driver. In the second phase, the real time traffic information will be used to adjust the optimal route along the way. State-of-the-art data warehousing and data mining techniques are applied to ensure efficiency of the system.